Program Keluarga Harapan Untuk Meningkatkan Kesejateraan Masyarakat (Studi di Desa Lanta Kecamatan Lambu Kabupaten Bima) - Hendra, Hendra; FIRMANSYAH, FIRMANSYAH; Budiman, Arif; Rizkiani, Firliah; Inayah, Nur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
In order to alleviate poverty, the government launched a special program called the Family Hope Program (PKH) related to this The implementation of the Family Hope Program in lanta village is based on the high number of poor households. It is hoped that the implementation of the Kelurga Harapan Program (PKH) can improve the welfare of the community in the fields of education and health. This study aims to find out how the implementation of the Family Hope Program (PKH) in an effort to improve community welfare in Lanta Kecamata Lambu Village, Bima Regency. This research uses a qualitative descriptive research method with a location in lanta village, Lambu district, Bima regency. Data collection techniques are carried out through observations, interviews and documents with the selection of informants by purposive sampling.